Analysis Of Fabric Inventory Control In Koko Clothing Busines With Economic Order Quantity and Economic Production Quantity Methods - Diharto, Ari; Andesta, Deny (Journal Knowledge Industrial Engineering (JKIE), 2022)
Ramli collection is an industry that is engaged in garments in producing special men's peddles, especially in koko clothes who want a good and fitting basic material arrangement. The product that will be researched is koko clothes. One of the problems in Ramli collection is the purchase of raw materials that are not good and appropriate. This study determines the optimal amount using the EOQ and EPQ methods. The research was conducted from January 2021 to December 2021. This study uses the EOQ and EPQ methods to determine the optimal calculation on raw materials of koko clothes, minimize inventory costs, determining Re-Order Points and fabric ordering costs. From the results of calculations with the EOQ method to get the optimal amount of raw materials for Catton Venus 184 roll and cattonferrari fabric 159 rolls. Calculation of the minimum inventory cost using the EOQ method on Catton Venus fabric Rp.55.877.600 and Catton Ferrari fabric Rp.42.445.640, calculation by EPQ method on Catton Venus fabric Rp.55.634.980 and Catton Ferrari Fabric Rp.42.220.070. The supply point (Re-Order Point) again occurs when the Catton Venus fabric is 20 rolls and the Catton Ferrari 16 roll fabric.